Analisis Zona Rawan Longsor Desa Molotabu, Kecamatan Kabila Bone, Kabupaten BoneBolango, Provinsi Gorontalo - Sutarto, Tiara Anggraeni Puspaningrum; Permana, Aang Panji; Hutagalung, Ronal (Universitas Negeri Gorontalo, 2025)
This study was conducted in Molotabu Village, Kabila Bone Subdistrict, BoneBolango Regency with the aim of analyzing landslide-prone zones. This study included Geographic Information System (GIS) analysis using ArcGIS for the assessment and determination of landslide hazard classes and the determination of the geological conditions of the study area, including geomorphology, stratigraphy, and geological structure. The methods used in this study included field surveys and the assessment and weighing of parameters that influence landslides. These parameters included lithology, rainfall, slope, land cover, and linear density. The lithology of the study area consisted of two rock units, namely the Dacite Rock Unit and the Tuff Rock Unit. Based on the results of the analysis of the landslide vulnerability class of Molotabu Village using the assessment and weighing method, three landslide vulnerability classes were obtained, namely a low landslide vulnerability class with an area of 0.11 km² and a relatively flat slope (7-15%), a medium vulnerability class with an area of 2.24 (Km)² (15-30%), and high landslide susceptibility class with an area of 0.84 〖Km〗² (30-70%).